Colonoscopy detects significantly more flat adenomas than 3-tesla magnetic resonance colonography: a pilot trial - Hüneburg, Robert; Kukuk, Guido; Nattermann, Jacob; Endler, Christoph; Penner, Arndt-Hendrik; Wolter, Karsten; Schild, Hans; Strassburg, Christian; Sauerbruch, Tilman; Schmitz, Volker; Willinek, Winfried (Endoscopy International Open, 2016)
Background and study aims: Colorectal cancer (CRC) is one of the most common cancers worldwide, and several efforts have been made to reduce its occurrence or severity. Although colonoscopy is considered the gold standard in CRC prevention, it has its disadvantages: missed lesions, bleeding, and perforation. Furthermore, a high number of patients undergo this procedure even though no polyps are detected. Therefore, an initial screening examination may be warranted. Our aim was to compare the adenoma detection rate of magnetic resonance colonography (MRC) with that of optical colonoscopy.Patients and methods: A total of 25 patients with an intermediate risk for CRC (17 men, 8 women; mean age 57.6, standard deviation 11) underwent MRC with a 3.0-tesla magnet, followed by colonoscopy. The endoscopist was initially blinded to the results of MRC and unblinded immediately after examining the distal rectum. Following endoscopic excision, the size, anatomical localization, and appearance of all polyps were described according to the Paris classification. Results: A total of 93 lesions were detected during colonoscopy. These included a malignant infiltration of the transverse colon due to gastric cancer in 1 patient, 28 adenomas in 10 patients, 19 hyperplastic polyps in 9 patients, and 45 non-neoplastic lesions. In 5 patients, no lesion was detected. MRC detected significantly fewer lesions: 1 adenoma (P = 0.001) and 1 hyperplastic polyp (P = 0.004). The malignant infiltration was seen with both modalities. Of the 28 adenomas, 23 (82 %) were 5 mm or smaller; only 4 adenomas 10 mm or larger (14 %) were detected.Conclusion: MRC does not detect adenomas sufficiently independently of the location of the lesion. Even advanced lesions were missed. Therefore, colonoscopy should still be considered the current gold standard, even for diagnostic purposes.